A signature-based secure interaction scheme for logistics management systems in the internet of things - Zhang, Zhenbo; Liu, Xingken; Gong, Lijiahui; Zhuang, Zhaoyu (Frontiers in Physics, 2025)
The rapid growth of e-commerce has been significantly driving the logistics industry’s development, while the speed of information technology transformation has laid a solid foundation for this progress. The Internet of Things (IoT), recognized as a representative of next-generation information technology, has injected new vitality into intelligent logistics management through its powerful data collection and transmission capabilities. The importance of user access control mechanisms has become increasingly evident in logistics management systems. Therefore, this paper proposes a signature-based authenticated scheme for logistics management systems. In this scheme, the user’s password, biometrics and smart card are used as the three authentication factors. During the login and authentication phase, registered users and devices in the logistics management system can securely and efficiently complete mutual authentication and key agreement. To verify the security performance of the proposed scheme, an simulation analysis is performed using the Scyther tool. Furthermore, performance evaluation demonstrates that the proposed scheme not only significantly enhances the security of the logistics management system but also maintains low costs.